Heritage statecraft and corporate power - Plets, Gertjan, author.
1 online resource (xiv, 214 pages)
Keywords: "Heritage Statecraft and Corporate Power examines the politicization of heritage and heritage conflicts in Siberia. In so doing, it challenges the idea that heritage is created by the state and instead argues that heritage creates the state. Building upon extensive ethnographic fieldwork undertaken in south-central Eurasia, this book provides an analysis of the sociopolitical enmeshment of archaeology and heritage in Russia's resource colony: Siberia. Although many examples from across Siberia are discussed, the core study region for the book is the Altai Republic, which is located where Russia, Mongolia, Kazakhstan and China intersect. Taking a "heritage statecraft" approach, Plets argues that heritage is a particularly important political instrument in this region. The book considers how different social "groups"--including Indigenous communities, Russian settlers, displaced groups, national and international archaeologists, political parties and energy companies--translate "objective" archaeological data into culturally distinct heritages. Plets encourages scrutiny of the different players that mobilize heritage to instill norms and ideas and the ways in which new regulations or institutions are ultimately implemented. Heritage Statecraft and Corporate Power contributes to key debates around the politics of archaeology, resource development and cultural heritage. It will be essential reading for academics and students engaged in the study of heritage, archaeology, and memory"--